General practitioners’ experiences of patients’ complaints: qualitative study - Jain, Ashok (British Medical Journal, 1999)
OBJECTIVE: To examine how general practitioners experience patients’ complaints. SETTING: General practices in Lambeth, Southwark, and Lewisham health authority. PARTICIPANTS: Representative sample of 30 general practitioners who had had complaints made against them under either the old or new complaints system. DESIGN: Qualitative study with detailed interviews. RESULTS: Participants described their experiences of patients’ complaints in three stages: initial impact, conflict, and resolution. The first stage described being out of control, feelings of shock and panic, and a sense of indignation towards patients generally. The second stage described the many conflicts generated by the complaint: emotional conflicts such as feelings of anger, depression, and even suicide, conflicts around aspects of professional identity including doubts about clinical competence, conflicts with family and colleagues, and conflicts arising from the management of the complaint. The third stage described a sense of resolution. For many this meant practising defensively, for others it meant planning to leave general practice, and for a minority no resolution was achieved. Not all participants, however, reported such a negative experience. Some described how they had become immune to complaints, and a small minority described the complaint as a learning experience. CONCLUSION: The initial impact stage and conflict stage may be necessary aspects of the experience that general practitioners endure when they have a complaint made against them. Support structures should, however, be in place to help general practitioners through these stages.